Islamic Education Learning Model from an Educational Psychology Perspective - Nada Nabila Az-Zahra; Muhibbin Syah; Bambang Samsul Arifin (al-Afkar, Journal For Islamic Studies, 2024)
A learning model is a blue print or pattern used to achieve educational goals. Learning models are strongly related to approaches, strategies and learning methods, all of which are oriented towards educational goals. Learning models are very diverse, teachers are free to choose the right learning model in the learning process, which is adapted to learning objectives, teaching materials, student conditions and class situations. , educators are required to have adequate knowledge about the material being taught, and also master various methods of delivery so that what is conveyed can be understood and comprehended by students. An educator or teacher's strategy in implementing learning has a strong impact on student achievement. Children learn through their experiences in the environment, both at home and at school.